Tax authorities’ access to information covered by banking secrecy with regard to the right to privacy - Sagan-Martko, Marta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
The institution of banking secrecy is regulated in legislation that is at the interface between the regulations of public and private law. This type of solution may lead to a conflict of interests ‒ private and public ones. The issue of tax authorities’ access to information covered by banking secrecy requires consideration in relation with the provisions of several legal acts. The procedure for obtaining information covered by bank secrecy provided for in Articles 182–185 of Tax Ordinance as well as the duty to take into account the principle of special trust between a client and a financial institution, are directives referring to the principle of conducting proceedings in a way that inspires trust in tax authorities, while the practice of making information available to tax authorities under Article 49(2) of the Act on the National Revenue Administration in fact deprives the parties of procedural safeguards. In the case of competitiveness of protected goods, it is necessary for the legislator to regulate the disputed issues in compliance with the constitutional requirements of standardisation and a clear and legible balance between the interests in conflict. It should therefore be concluded that when introducing new legislation on the matter of interference in the right to privacy, the legislator is obliged to balance the competing valuses with particular care. The balance between the taxpayer's privacy and the public interest does not seem to have been preserved in the scope of the subject matterin question.

Instytucja tajemnicy bankowej uregulowana została w przepisach znajdujących się na styku regulacji publiczno- i prywatnoprawnych. Tego rodzaju rozwiązanie może prowadzić do konfliktu interesów – prywatnego oraz publicznego. Problematyka dostępu organów podatkowych do informacji objętych tajemnicą bankową wymaga rozważenia w powiązaniu z przepisami kilku aktów prawnych. Procedura uzyskania informacji objętych tajemnicą bankową przewidziana w art. 182–185 Ordynacji podatkowej, a także obowiązek wzięcia pod uwagę zasady szczególnego zaufania między klientem a instytucją finansową to dyrektywy nawiązujące do zasady prowadzenia postępowania w sposób budzący zaufanie do organów podatkowych, natomiast praktyka udostępniania organom podatkowym informacji na podstawie art. 49 pkt 2 ustawy o Krajowej Administracji Skarbowej w istocie pozbawia strony gwarancji procesowych. W przypadku konkurencyjności chronionych dóbr konieczne jest uregulowanie przez ustawodawcę spornych kwestii z zachowaniem konstytucyjnych wymogów normowania oraz jasnej i czytelnej równowagi między interesami pozostającymi w kolizji. Należy zatem stwierdzić, że przy stanowieniu przepisów odnoszących się do materii, jaką jest ingerencja w prawo do prywatności, ustawodawca jest zobligowany do szczególnie starannego wyważenia konkurujących ze sobą wartości. Wydaje się, że w zakresie omawianej problematyki równowaga pomiędzy prywatnością podatnika a interesem publicznoprawnym nie została zachowana.
Dostęp organów podatkowych do informacji objętych tajemnicą bankową a prawo do prywatności
Keywords: banking secrecy; taxpayer; tax authorities; access; privacy; tajemnica bankowa; podatnik; organy podatkowe; dostęp; prywatność